Penanganan Tindak Kekerasan Dalam Rumah Tangga di Kelurahan Bonto Perak Kecamatan Pangkajene Kabupaten PANGKEP - Hambali H Husaini; St Harlina; Habiba; Djunarti; Haryati Wagiman; Fahrisal Husain (ADPERTISI, 2023)
Divorce cases in Pangkep Regency are caused by disputes between husband and wife that occur continuously so that they feel that there is no longer a match for each other.